A Randomized Controlled Trial on the Effectiveness of FITT Principle In Increasing VO2 Max - Muh. Isna Nurdin Wibisana; Ibnu Fatkhu Royana (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objectives. This study utilized students from the University of PGRI Semarang who were majoring in physical education and health recreation. The study aimed to apply the Frequency, Intensity, Time, and Type (FITT) training method to design and manage physical exercise programs that would help achieve specific fitness or sports objectives. The primary focus of the study was to increase VO2 max by utilizing the FITT principle. Materials and method. The study employed a quantitative research method with a pre-experimental design, specifically a randomized controlled trial with a pretest-posttest. The research involved 160 participants and utilized the Multi Fitness Test (MFT) to measure lung capacity endurance or VO2 max. The implementation of the FITT principle treatment led to improved aerobic endurance, as evidenced by the results of the pretest and posttest. Result. The results of the paired samples test showed that the significance level is less than 0.05, indicating that the alternative hypothesis (Ha) is accepted. This suggests that there is a considerable impact of the FITT method on enhancing the VO2 max capacity of respondents. The study revealed an 18% increase in VO2 max capacity from the pretest to the post-test. Conclusion. The study conducted has demonstrated that implementing FITT principles in an exercise program in a systematic manner has resulted in a remarkable enhancement of VO2 max capacity. Furthermore, this model can serve as a substitute method for instructors and educators to impart knowledge and training.